Cutaneous Vasculitis, Interstitial Pneumonia with Crazy-Paving Appearance, and Positive pANCA in a Patient with Severe Crohn’s Disease - Guang-liang Chen; Juan Wang; Bao-zhen Li; Li-mei Li; Han-you Mo; Shuang Ye (Case Reports in Gastrointestinal Medicine)
Cutaneous vasculitis, interstitial pneumonia with crazy-paving appearance on high-resolution computed tomography, and repeated positive perinuclear anti-neutrophil cytoplasmic antibodies (pANCA) are rarely found together in patients with inflammatory bowel disease in the existing literature. We report the case of a Chinese patient previously diagnosed with cutaneous vasculitis and interstitial pneumonia, who presented with acute pain and mass in his right lower quadrant a couple of years later. The terminal ileum biopsy and postoperative pathology confirmed Crohn’s disease (CD).